Rethinking context models - Pérez, Emiliano; Fortier, Andrés; Rossi, Gustavo Héctor; Gordillo, Silvia Ethel (2009)
Since the first context-aware applications were designed, context modelling has played a central role. During the last decade many different approaches were proposed to model context, ranging from ad-hoc models to extensions to relational databases or ontologies. In this paper we propose to take a step back and analyse those approaches using the seminal views presented by Paul Dourish in his work (What we talk about when we talk about context). Based on that analysis we propose a set of guidelines that any context model should follow.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Confederated International Workshops and Posters, ADI, CAMS, EI2N, ISDE, IWSSA, MONET, OnToContent, ODIS, ORM, OTM Academy, SWWS, SEMELS, Beyond SAWSDL, and COMBEK (2009, Nov.,1-6:Vilamoura, Portugal).Proceedings Berlín : Springer, 2009. (Lecture Notes in Computer Science; 5872), pp. 78-87.
Keywords: ARQUITECTURA DE SOFTWARE; COMPUTACIÓN UBICUA